THE PROJECT-BASED LEARNING TECHNOLOGY IN THE METHODOLOGY OF TEACHING UKRAINIAN LANGUAGE FOR PROFESSIONAL PURPOSES - Humeniuk, Iryna (Mountain School of Ukrainian Carpaty, 2021)
The article focuses on studying the potential of application of the project-based technology in the process of teaching Ukrainian Language for Professional Purposes to future specialists in the pedagogical sphere. In order to achieve the aim of the research, a set of methods has been used: analysis and systematization of scientific sources to elucidate the stage of solving the issue; visualization and generalization to clarify the stages of implementation of the research approach and define the theme of the project-based activity of students within the Ukrainian Language for Professional Purposes course. The methodology of using informational, applied and research projects within the analyzed teaching technology is emphasized. On the basis of analysis of the scientific information space of the issue, the main types of project-based activity that can be used in the process of teaching Ukrainian Language for Professional Purposes have been determined, their aim and consistency with the stages of implementation of the research approach in the context of the analyzed academic discipline have been established. The author’s view of the gradual implementation of the research approach in the context of teaching Ukrainian Language for Professional Purposes has been taken as the basis for creation of the theme of the projectbased activity within the discipline, and the main conditions for efficiency of implementation of the project-based learning technology within the course are emphasized: the prospective form of task statement, professional direction of the themes of projects with outlines of their applied use, a clear algorithm of implementation, assessment criteria, and compulsory public presentation of results. It is pointed out that the content and the algorithm of projecting depict the main aspects of teaching through research and therefore are the fundamental method of implementation of the research approach in the context of Ukrainian Language for Professional Purposes.